Comparison of the Effectiveness of the Acceptance-Commitment-Based Approach and Group-Choice Theory in Adolescent Anxiety Syndrome - Bahrami , Afsaneh; Dokanehi Fard , Farideh; Mirhashemi , Malek (Applied Family Therapy Journal (AFTJ), 2020)
Aim: The study was performed to compare the effectiveness of the educational intervention of the acceptance-commitment-based approach and the group choice theory approach in adolescent anxiety syndrome. Method: This was a quasi-experimental study with pretest-posttest design, control group, and one-month follow-up. The statistical population included all female second-grade high school students in District 5 of Tehran in the academic year of 2019-2020, from which 30 students were selected by convenience sampling and assigned to two experimental groups and one control group (10 people in each group). The experimental group received Hayes et al.’s (1999) acceptance-commitment-based therapy, and the experimental group received Sahebi’s choice theory education therapy (2015) in two sessions per week for ten 90-minute sessions. The study tool was the Cattle Anxiety Questionnaire (CAQ) (1958). Data were analyzed using repeated-measures ANOVA. Results: The results showed that the acceptance-commitment-based approach (F = 6.38, P = 0.022) and choice theory affected anxiety score (F = 6.73, P = 0.019) and that this effect was stable in the follow-up phase. Conclusion: Since choice theory had a greater effect on adolescent anxiety syndrome than the acceptance-commitment-based approach, it could be recommended that this approach be used to reduce anxiety syndrome, especially for adolescents.